Implementasi Peraturan Bupati Sintang Nomor 66 Tahun 2020 Tentang Sistem Online Pajak Daerah Di Kabupaten Sintang - Ryan Maynaki; Sri Maryuni; Ida Rochmawati (Professional: Jurnal Komunikasi dan Administrasi Publik, 2026)
This research aims to analyze the implementation of Sintang Regent Regulation Number 66 of 2020 concerning the Regional Tax Online System. The background of this study is the still low level of effectiveness in the implementation of the online tax system in Sintang Regency, which impacts the suboptimal contribution to Local Own-Source Revenue (PAD). The research method uses a descriptive research type with a qualitative approach. The results of the study indicate that policy implementation is still facing various constraints. The communication factor has not been evenly distributed to Taxpayers. The resource factor, both budgetary resources and human resources, is not yet optimal. The disposition of implementers factor shows a sufficient level of enthusiasm and strong commitment in supporting policy implementation. The bureaucratic structure factor shows that formally, the Sintang Regency Regional Revenue Agency (Bappenda) organization has a good structure and coordination flow.